Emergy Analysis of Agricultural Ecosystem in Shouguang City, Shandong Province. Issue 1 (November 2020) - Mu, Lin; Wang, Yan; Zhao, Tianhong; Ma, Jian
Abstract: By using the method of emergy analysis, this paper analyzed agricultural industrial structure and the emergy input, output and emergy index of agricultural ecosystem in Shouguang City from 2007 to 2016, which reflected the development trend of agricultural ecosystem. The results showed that the total emergy input of agricultural ecosystem in Shouguang City from 2007 to 2016 was in a downward trend, and the change trend of total emergy output was in a downward and then upward trend. From the emergy index, the economic input of agricultural ecosystem in Shouguang City was large, the environmental utilization was not sufficient, but the pressure on the environment was small, and the agricultural ecosystem in Shouguang City was in a sustainable state Continuous development status.